Uncertainties in the permittivity model for seawater in FASTEM and implications for the calibration/validation of microwave imagers. (March 2020) - Lawrence, Heather; Bormann, Niels; English, Stephen J.
Highlights: Estimated uncertainties in the FASTEM permittivity model are 0.5 - 2K at 6 - 90 GHz. FASTEM agrees with permittivity measurements within uncertainties at 23 - 90 GHz. Differences between FASTEM and permittivity measurements are observed at 6 - 19 GHz. A better fit to 6 - 19 GHz measurements leads to increased bias in satellite O - B. Abstract: This paper evaluates uncertainties in the ocean permittivity model needed to compute surface emission and reflection, at frequencies of 6 - 90 GHz. The study transforms permittivities and laboratory measurement uncertainties into typical brightness temperatures for microwave imagers. It is established that the permittivity model used by FASTEM agrees with the laboratory measurements to within their published uncertainties at frequencies of 23 GHz, 37 GHz and 89 GHz, but this is not the case at 6.8, 10.65 and 18.7 GHz, particularly at low temperatures. The laboratory measurement uncertainties transformed into typical brightness temperatures are reported and compared to observation minus short-range forecast (O - B) differences for microwave imagers for a range of ocean surface skin temperatures. For GMI and AMSR-2 these differences show very little skin-temperature dependent bias when calculated using FASTEM. However, when a new version of the permittivity model is used in FASTEM, that fits the low-frequency laboratory data better, an increase in skin temperature dependent bias is observed for channels at 10 - 23 GHz that is larger than the stated measurement uncertainties. This suggests that either the laboratory measurements have additional sources of systematic error at low frequencies, or there are additional sources of bias in the mean O - B calculations for microwave imagers that are currently masked by biases in FASTEM. To resolve this, reference-quality measurements of seawater permittivity are needed at all relevant microwave frequencies and temperatures, particularly at low temperatures and low frequencies.